Anthropometric Measures and Incident Diabetic Nephropathy in Participants With Type 2 Diabetes Mellitus - Hukportie, Daniel Nyarko; Li, Fu-Rong; Zhou, Rui; Zheng, Jia-Zhen; Wu, Xiao-Xiang; Wu, Xian-Bo (Frontiers in Endocrinology, 2021)
Background: The prevalence of diabetes is on the rise globally coupled with its associated complications, such as diabetic nephropathy (DN). Obesity has been identified as a risk factor for the development of DN but it is still unclear which obesity index is the best predictor of incident DN. Methods: Data from the participants with type 2 diabetes mellitus (T2DM) in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study were used to examine the sex-specific association between waist circumference (WC), waist-to-height ratio (WHtR), and body mass index (BMI) with incident DN risk. Results: Among the 8,887 participants with T2DM (5,489 men and 3,398 women), 5,296 participants (3,345 men and 1,951 women) developed the DN composite outcome during a follow-up period of 24302 person-years. Among men, null associations were observed between all anthropometric measures with incident DN in the multivariate analysis although the 3rd quartile of WHtR showed marginally significant results (P = 0.052). However, among women, both central and general obesity measures were associated with increased risks of incident DN. Compared with participants in the WC <88 cm category, the fully adjusted HR and 95% CI for those in the ≥88 cm of WC was 1.35 (95% CI 1.15-1.57). Compared with the lowest quartile, the fully adjusted HRs and 95% CIs for the 2nd to the 4th quartile of WHtR were 1.09 (95% CI 0.96-1.25), 1.12 (95% CI 0.98-1.28), and 1.14 (95% CI 1.00-1.30) respectively; also, compared with the normal BMI category, the fully adjusted HRs and 95% CIs for class I – class III obese were 1.36 (95% CI 1.10 – 1.67), 1.43 (95% CI 1.16 – 1.78) and 1.32 (95% CI 1.05 – 1.66) respectively. Conclusions: Among participants with T2DM, higher levels of both central and general obesity indexes were associated with DN risk among women but not in men. Women with T2DM should maintain a healthy weight targeted at reducing both central and general obesity to enhance nephroprotection. Trial registration: ClinicalTrials.gov., no. NCT00000620.